Programmed english : a preliminary testing of a branching programme constructed for the use of English lower canditates in standard 6 on the order of the adverbial modifiers of place, time, manner and frequency - Meintjes, Clive Rudolph (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1971.